(untitled) (TAJ: Journal of Teachers Association, 2010)
Epilepsy is a common neurological problem in children. A retrospective study was carried out among the epileptic children attending in the child development and Neurology service center of the department of Pediatrics of Bangabandhu Sheikh Mujib Medical University, Dhaka over a period from September 1999 to September 2001. The aim of this study was to find out clinical profile of epilepsy in children attending in a tertiary care hospital. One hundred twenty children of 1 month to 15 years of age of both sexes were included. Febrile seizures and seizure due to acute CNS infection were excluded from the study. This study showed that epileptic children were mostly from urban area (58%) with M&F 3.14:1 and 50% of them between 1-5 years of age with mean age 2.67 years it was found that most of the children were term (86.55%); home delivered (67.80%), normal birth weight (86.55%), history of delayed crying (43.78%) and history of resuscitation (24.00%). Majority of the patients had perinatal history of irregular and no antenatal check up 51.25%. Common age of onset of seizures was found in the most cases (57.75%) before 1 year of age. GTCS (48.27%) was the commonest pattern of seizure. Epileptic children were mostly severe type (71.70%), which were associated with daily seizure discharged (66.67%). Some of the patients (39.53%) were associated with known provoking factors. Gross motors (58.62%) were the common associated impairment or disability of the epileptic patients. About one third of the patients (32.46%) were associated with cerebral palsy where quadriplegic type was common 48.65%). A significant number of patients (44.8%) were treated previously with AEDs. Among them 60% were treated with single drug. Fifty one percent of the epileptic children were treated inadequately. After attending in the neurology center 69.25% of the patients were getting mono therapy and polytherapy was given in 30.48% of the patients. Carbamazipine and Valproate were commonly used in initial treatment. After initial treatment, control of seizures occurred in 54.25% of cases at different duration. With poly therapy 22.22% of patients did not response with AEDs. During the study period total 26 patients were remain seizures free at different duration. TAJ 2010; 23(1): 46-50